ARTHUR SCHOPENHAUER – TRDOVRATNI ČLOVEK MORALE (Philological Studies, 2019)
The paper is an analysis of Schopenhauer’s metaphysical views that made Nietzsche develops a permanent belief in the ideal of Schopenhauer’s human being. What is common to both and important in the framework of the present-day world that seeks very much to restore ethics Schopenhauer’s and Nietzsche’s conviction that ethics should be conceived of as man’s “second nature” rather than “anti-nature,” as used to be the case in the past. Schopenhauer is clearly more convincing in the metaphysical sense, because he commands an attitude to the most mysterious and the most profound foundations of being. The contemporary human being feels closer to Nietzsche’s side because of the mental closeness. Nietzsche was not driven so much by the metaphysical need, but rather by the moralistic need; not by the essence of being but the essence of man’s soul and of its ethical passion. In Schopenhauer and Nietzsche both the metaphysics of solitude and the ethics of being on one’s own are located within the metaphysical tradition which means that self-awareness and cognizance of the world constitute a uniform and inseparable process. It is in the post-metaphysical substantiation of mind and philosophy that this process disintegrates, the theory of reality and the ethical theory become separated, each going on to develop further in its own way.